Psychometric evaluation of the indonesian version of the holistic nursing competence scale (HNCS) - Maria Silvana Dhawo; Maria Frani Ayu Andari Dias; Muhammad Rifa'at (Universitas Airlangga, 2026)
Introduction: The global demand for high-quality care requires valid, holistic instruments, especially in developing healthcare systems such as Indonesia, where existing tools are often fragmented. This study aimed to translate, culturally adapt, and validate the Indonesian version of the Holistic Nursing Competence Scale by evaluating its psychometric properties. Methods: This study employed a cross-sectional descriptive design, sampling 208 registered nurses with a minimum of two years’ experience from adult inpatient wards across Kalimantan Island. The instrument underwent rigorous forward-backward translation and expert review, achieving excellent content validity (S-CVI/UA = 0.99). Results:Data factorability was confirmed by a high Kaiser-Meyer-Olkin (KMO) value of 0.962 and a significant Bartlett’s test (p < 0.001). Exploratory Factor Analysis (EFA) extracted a robust three-factor structure, accounting for 69.1% of the total variance. These factors were identified as Competence in Professional Nursing Practice, Leadership and Professional Development, and Self-Reflection and Personal Growth. The Indonesian HNCS demonstrated high internal consistency, with Cronbach’s alpha coefficients of 0.981, 0.953, and 0.872 for factors 1, 2, and 3, respectively. Conclusions: The Indonesian version of the HNCS is a valid and highly reliable instrument, providing a standardized, contextually relevant framework for accurately measuring holistic nursing competence and addressing a critical national measurement gap.